Defense against predators incurs high reproductive costs for the aposematic moth Arctia plantaginis. (15th April 2020) - Lindstedt, Carita; Suisto, Kaisa; Burdfield-Steel, Emily; Winters, Anne E; Mappes, Johanna
Abstract: To understand how variation in warning displays evolves and is maintained, we need to understand not only how perceivers of these traits select color and toxicity but also the sources of the genetic and phenotypic variation exposed to selection by them. We studied these aspects in the wood tiger moth Arctia plantaginis, which has two locally co-occurring male color morphs in Europe: yellow and white. When threatened, both morphs produce defensive secretions from their abdomen and from thoracic glands. Abdominal fluid has shown to be more important against invertebrate predators than avian predators, and the defensive secretion of the yellow morph is more effective against ants. Here, we focused on the morph-linked reproductive costs of secretion of the abdominal fluid and quantified the proportion of phenotypic and genetic variation in it. We hypothesized that, if yellow males pay higher reproductive costs for their more effective aposematic display, the subsequent higher mating success of white males could offer one explanation for the maintenance of the polymorphism. We first found that the heritable variation in the quantity of abdominal secretion was very low ( h 2 = 0.006) and the quantity of defensive secretion was not dependent on the male morph. Second, deploying the abdominal defensive secretion decreased the reproductive output of both color morphs equally. This suggests that potential costs of pigment production and chemical defense against invertebrates are not linked in A. plantaginis . Furthermore, our results indicate that environmentally induced variation in chemical defense can alter an individual's fitness significantly. Abstract : How much does it cost to defend against predators? A lot if you are a male wood tiger moth as deploying their defensive secretion decreases their reproductive success. When threatened, these aposematic moths produce defensive secretions from their abdomen, which are targeted specifically against invertebrate predators. However, this invertebrate-specific defense does not come without costs: deploying the defensive secretion only once decreases the reproductive success of males.